PRODUCTION IN BACTERIAL CELL A RECOMBINANT ANALOG OF PROINSULIN WITH THE PROPER DISULFIDE BONDS - Ponomarenko, S.; Bouchaala, Ch. (Eurasian Journal of Applied Biotechnology, 2014)
Mechanism of molecular folding of polypeptides synthesized in animal cells, is fundamentally different from the set found in prokaryotes and yeasts, which are traditionally used in the biopharmaceutical industry for expression of recombinant human proteins. The recombinant proteins expressed in a bacterial host system are chemically refolded in vitro to form their correct conformations. Arrangement of disulfide bridges is essential for the process of molecular folding of polypeptides into their three-dimensional structure and, eventually, for the formation of native protein conformation required for biological activity. Here is described a new technology of protein expression in bacteria, exploiting prokaryotic system to fold of recombinant polypeptides with formation of correct disulfide bonds. According this technology, human insulin - important therapeutic protein - can be obtained without chemical refolding from recombinant analog of preproinsulin synthesized in bacteria. This is realized by creation in host cell of polypeptide structure with correct thiol bonds in cystine, which are analogous of disulfide bridges found in transit form of proinsulin. According to the new technology, recombinant protein is expressed at a concentration sufficient for biosynthesis of the heterogeneous membrane protein in Escherichia coli cells. This semifolded proteopeptide is protected from proteolytic degradation, and it may be isolated as a complex similar to the proinsulin transit form. Transit forms of proinsulin are required for further transformation of hetero-dimer molecules into the native proteohormone structure. The new method without chemical refolding prevents accumulation of isoforms, significantly reduces time and material costs by production of recombinant human insulin in its native conformation.